Evaluation of Plasma Alpha Klotho Levels in Obese Cases: Plasma Alpha Klotho Levels in Obese Cases - Solak, Ibrahim; Guney, Ibrahim; Sekmenli, Nevin; Kurku, Huseyin; Eryilmaz, Mehmet Ali (Journal of Medical Biochemistry, 2026)
Background: Klotho is an anti-aging gene that lengthens life when excessively expressed and accelerates aging when disrupted. In our study, we will research the correlations between plasma α-Klotho (α-KL) protein levels with body mass index (BMI), carotid intima media thickness (CIMT), total antioxidant status (TAS), total oxidant status (TOS), oxidative stress index (OSI), high-sensitivity c-reactive protein (hsCRP) and cholesterol values in obese patients. Methods: This study was conducted in a single-centered and cross-sectional manner. Results: The study was performed with a total of 90 participants, 35 women (38.9%) and 55 men (61.1%). Of participants included in the study, 30 were normal weight (33.3%) (Group 1), 30 were overweight (33.3%) (Group 2) and 30 were obese (33.3%) (Group 3). There were statistically significant differences in the α-KL protein (p=0.010), hsCRP (p<0.001), homeostasis model assessment of insulin resistance (HOMA-IR) (p=0.022), values of the study groups. There is no significant difference between the study groups in terms of CIMT (p=0.380), TOS (p=0.613), TAS (p=0.056) and, OSI (p=0.943) values. Conclusions: In conclusion, in this study, the overweight group had α-KL protein values that were significantly higher than the obese group, while hsCRP values were significantly higher in the obese group compared to the overweight and normal weight groups. There were no significant differences for CIMT, TAS, TOS and, OSI values in the study groups. There were no significant correlations between α-KL protein values with BMI, hsCRP, CIMT, TAS, TOS and OSI values of participants in the study.